Pengaruh Praktik Kewirausahaan dan Ekspektasi Pendapatan terhadap Minat Berwirausaha Siswa SMK Negeri 62 Jakarta - Abdullah Azzam; Henry Eriyanto; Maulana Amirul Adha (Mutiara : Jurnal Penelitian dan Karya Ilmiah, 2025)
Indonesia still faces serious challenges in the employment sector, marked by a relatively high unemployment rate. One group contributing to the highest unemployment rate are vocational high school (SMK) graduates, who, ironically, are prepared to enter the workforce directly. This high unemployment rate indicates a gap between graduate competencies and the needs of the workforce, as well as a lack of mental readiness and entrepreneurial skills. One strategic solution to address this problem is to encourage young people, particularly vocational high school students, to become entrepreneurs. In this context, entrepreneurial practices and income expectations are two important variables believed to increase entrepreneurial interest among students. This study aims to examine the contribution of entrepreneurial practices and income expectations in increasing entrepreneurial interest among vocational high school students. The research method used was quantitative, with primary data collection through an online survey. The instrument used was an online questionnaire compiled using a Likert scale and distributed through Google Forms. Respondents in this study were 188 vocational high school students selected using a proportional random sampling technique based on the Taro Yamane table, so that the data obtained can proportionally represent the population. Data analysis was performed using Smart PLS (Partial Least Squares) software. The analysis results show that entrepreneurial practices have a positive and significant direct effect on income expectations. Furthermore, entrepreneurial practices also have a positive and significant direct effect on entrepreneurial interest. Income expectations were found to have a positive and significant direct effect on entrepreneurial interest. Furthermore, entrepreneurial practices were also found to have an indirect effect on entrepreneurial interest through income expectations as a mediating variable. These findings emphasize the importance of implementing concrete and structured entrepreneurial practices in the vocational high school curriculum.